Synthesis and biological evaluation of potential DNA cross-linking agents based on pyrrolizidine alkaloids - Kosogof, Christi, author; Williams, Robert M., advisor (Colorado State University. Libraries, 2001)
DNA cross-linking agents represent one of the most potent categories of antitumor agents. Pyrrolizidine alkaloids are an abundant class of biologically active natural products. These alkaloids display high levels of DNA cross-linking ability, and could have potential use as antitumor agents. Unfortunately, the high levels of hepatotoxicity induced by these compounds negates their effectiveness as antitumor agents. Modification of the chemical structure of the pyrrolizidine core could yield compounds with potent antitumor activity and reduced hepatotoxicity. The synthesis of a class of potential pyrrolizidine progenitors developed from monocrotaline is discussed. The synthesis of a potential water soluble photolabile protecting group is also described. In addition, the biological evaluation of the synthesized pyrrolizidine progenitors was investigated.
Keywords: Pyrrolizidines; Antineoplastic agents